Spatiotemporal expression profiling and molecular characterisation of miR-344b and miR-344c in the developing mouse brain - Leong, Jia Wen; Abdullah, Syahrilnizam; Ling, King Hwa; Cheah, Pike See (2015)
MicroRNAs are small non-coding RNAs of about 22 nucleotides that regulate gene expression through inhibition or repression processes during post-transcriptional or translational stages. Studies have shown that miRNAs play a crucial role in spatiotemporal regulation of the brain development. A recent study had shown that miR-344 is expressed in a developing mouse brain. In this study, we focused to characterise the spatiotemporal expression of miR-344b and miR-344c during the development of mouse brain. Out in situ hybridisation studies have shown that both miR-344b and miR-344c were strongly expressed in the germinal layer during the early stages of mouse brain development. Postnatally, expression of miR-344b was not detectable in P1 and adult brains. In contrast, miR-344c was expressed globally in P1 brain and was expressed exclusively in the olfactory bulb and granular cell layer of the cerebellum in the adult mouse brain. A subsequent stemloop RT-qPCR analysis showed that expression of the miR-344b and miR-344c was increased from E11.5 and peaked at E15.5. Postnatally, expression level of the miR-344b was reduced while miR-344c continued to express until adulthood. We further investigated the expression of miR-344b and miR-344c in adult mouse multiple organs and the pancreas showed the highest expression for both miRNAs. Subsequent bioinformatics analysis predicted that miR-344b and miR-344c were found to target a total of 1540 and 863 downstream target genes respectively. Genes associated with transcription regulation and nervous system development were subjected to further screening. We found that Olig2 and Otx2 were predicted as the potential downstream target gene for miR-344b and miR-344c respectively. However, luciferase protein suppression assay showed that the expression of Olig2 and Otx2 were not suppressed by overexpression of miR-344b and miR-344c. In conclusion, miR-344b and miR-344c were expressed in the developing mouse brain and may play a role during early mouse brain development although not directly targeting Olig2 and Otx2.